Pengaruh Puasa Ramadhan Terhadap Rerata Massa Lemak Tubuh Dan Indeks Massa Tubuh Pada Remaja Fase Akhir - Illahika, Anung Putri; Noerwahjono, Abi; Munawaroh, Endis Lailatul Qodri; Primananda, Akbar (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2023)
In body composition, we can find out whether a person's nutritional status is obese or not. Where we know that obesity increases the risk of non-communicable diseases such as diabetes mellitus, cardiovascular disease, and cancer. One method that can help reduce the possibility of these problems is fasting. A method that one of the goals is to rest the body, especially the digestive system, and get rid of harmful toxins in the body. This study aims to determine the effect of Ramadan fasting on fat mass and body mass index in late adolescence. This research is an analytic observational research with Cross Sectional method. The sample in this study was a student of FK UMM who served as an assistant lecturer in the biomedical laboratory. The analytical test used is the Friedmen and Wilcoxon tests. The results obtained include: (1) The average BMI of respondents is 23.94 Â± 4.3 and the majority are classified as having a normal BMI of 56.7%. While the average fat mass (%) was 28.56 Â± 9.15 and the majority were in the obese category (50%). (2) there was an increase in BMI in week 2 of the Ramadan Fasting but only slightly, then at week 3 it was obtained an average that was almost the same as the first week of the Ramadan Fast. Friedman test results resulted in p value = 0.472. (3) Wilcoxon test to determine the effect of fasting in each week obtained a significance value of more than 0.05. (4) Friedman test results to determine the effect of Ramadan fasting on body fat mass, the p value = 0.145. In conclusion,Ramadan fasting has no effect on body fat mass and body mass index.